INDISCRIMINATED INDICATION USE OF SILDENAFILA AND TADALAFILA BY YOUNGERS - Rezende, Patrícia Mendes (2021)
Erectile dysfunction (DE) is known as a man's difficulty in obtaining or maintaining an erection, may have as causes some diseases and conditions such as: depression, diabetes, arterial hypertension, high cholesterol, obesity, coronary disease, disease of Parkinson's, prostate cancer treatment, anabolic steroid consumption, spinal cord injuries, drug addiction, alcoholism, and even stress and anxiety. An accidental discovery of one of the most famous pharmaceuticals in the pharmaceutical industry began at the end of the 80, when the American laboratory Pfizer, who had invested heavily in research and testing to find a drug for hypertension Pulmonary and angina pectoris. So, these studies were terminated in 1992, because the first results suggested that the drug had a small effect on angina. However, it was noted some properties in the Sildenafil citrate that could be a new light on the treatment of erectile dysfunctions. In the 30-day period, in the region's drugstores, approximately 800 individuals aged between 17 and 85 years were treated, where it can be verified that not only people with erectile dysfunction make use of sildenafil and tadalafila. Where 51% of these individuals aged between 17 and 30 years make use of these regular medications, in most cases if they are for recreational use, without a medical indication only for personal reasons such as: increase libido and improve sexual performance.